Прізвища з поліфункційними формантами в антропоніміконі півдня Волинської області - Лісова, Лариса; Lisova, Larysa (Східноєвропейський національний університет імені Лесі Українки, 2015)
У статті проаналізовано прізвища з поліфункційними формантами в сучасному антропоніміконі півдня Волинської області. Для групи прізвищ із поліфункційними формантами характерна найбільша різноманітність афіксів (17 формантів). У кількісному плані домінують антропоніми з суфіксами -ук (-’ук, -чук), -ськ-ий, -к(о), -ик та інші. Охарактеризовано продуктивність суфіксів у творенні прізвищ, встановлено семантику їхніх основ. In the article the last names are analysed with polifunktional formants in modern anthroponomastics south the Volyn area. The specific of anthroponomastics of every region consists in quantitative and high-quality correlation of the last names with certain suffixes, predefined linguistic, in particular dialectal reasons, by the features of forming of language. As early as times of creation of the names of polifunktional suffixes began to execute a basic function – to specify that is mentioned is a descendant of person, mentioned in formative basis. In the anthroponomy of the south in Volyn region the last names of morphological type dominate, among which anthroponyms with polyfunctional formants prevail. The last names with polifunktional formants occupy a considerable place in south the Volyn area. The productivity of suffixes is described in creation of the last names, semantics of their bases is set. The semantics of bases and word-formation structure of the modern last names in the south of Volyn region reflect common Ukrainian tendencies of anthroponomical system, and also regional features of anthroponomy, predefined by the specific of the development of dialects, interlingual links, history, culture, way of life of the region.
Surname with Polifunktional Formants in Anthroponomastics of Sonth Part of the Volyn Area
Keywords: прізвище; суфікс; ім’я; антропонім; апелятив; surname; suffix; name; anthroponym; appelative